The Evolving Role of the Planning Function : International Experience and Reform Options for India - World Bank (World Bank, Washington, DC, 2021)
This note presents the main trends in strategic planning across public sector administrations in seven countries: Australia, Canada, Brazil, Mexico, Malaysia, South Korea, and Colombia. It was prepared in response to the Indian Government's interest in understanding the emerging trends in the evolution of strategic planning in a range of countries and effectively adapting this function across public administration at the national and subnational levels.